El uso de classdojo y su influencia en el proceso de aprendizaje en los niños con dislexia de la Unidad Educativa Ab. Jaime Roldós Aguilera, Montalvo - Peña Vega, Dolores Eugenia (2022)
Worldwide, dyslexia is considered as a learning disability by some specialists or as a disorder in reading ability by others, which is why the objective of the research is to determine how the use of ClassDojo influences the process. learning in children with dyslexia. The design was applied experimentally, of a pre type, a first moment a pre test to the students with dyslexia of the educational institution identified by the corresponding institutional office, after reinforcement sessions through the Classdojo platform a post test was taken. The results showed that the student with dyslexia adapts easily to the new work process on the platform, accesses information more easily, has a higher appreciation for the learning achieved through the platform, than awards or incentives for achievements. achieved motivate their learning, they are motivated to a permanent participation in classes improving their learning and develop a collaborative dynamic that generates security in their learning. Concluding that the way in which the variables use of Classdojo and the learning process are related is Medium, with a correlation of paired samples: Moderate, with which it is evident that a greater and better use of the Classdojo platform will obtain a better learning process by children with Dyslexia in the Jaime Roldós Aguilera de Montalvo educational unit.